Voiding symptom severity varies independently from non-adrenergic prostate smooth muscle contractions in patients undergoing surgery for benign prostatic hyperplasia - Keller, Patrick; Hu, Sheng; Nicola, Philip; Berger, Laurenz; Tamalunas, Alexander; Weinhold, Philipp; Stief, Christian G.; Hennenberg, Martin (Frontiers in Physiology, 2025)
BackgroundResistance of voiding symptoms to α1-blockers in benign prostatic hyperplasia (BPH) has been provisionally explained by non-adrenergic prostate smooth muscle contraction. Here, we examined relationships between contractions and voiding symptoms in prostate tissues from laser-enucleation.MethodsTissues were obtained from holmium and thulium laser enucleation. Contractions were induced by endothelin-1, U46619, noradrenaline and electric field stimulation (EFS). Emax values were analyzed for correlation with international prostate symptom score (IPSS), and compared to tissues from patients without surgery for BPH.ResultsNoradrenaline- and EFS-induced contractions were higher with severe (IPSS 20–35) than moderate symptoms (IPSS 8–19) (Emax noradrenaline 66% vs 113% of KCl-induced contractions; EFS 33% vs 66%). Endothelin-1- and U46619-induced contractions were already maximum with moderate symptoms (endothelin-1 117% moderate, 135% severe; U46619 23%, 27%). Within 8–21 points, IPSS increased with Emax values for noradrenaline and EFS (r = 0.545, r = 0.448), but not with endothelin-1- or U46619-induced contractions. Endothelin-1-induced contractions were similar to noradrenaline-induced contractions (Emax endothelin-1 126% of KCl, noradrenaline 96%), and exceeded EFS- (52%) and U46619-induced contractions (25%). Emax values for endothelin-1 were similar between laser-enucleated patients and patients without surgery for BPH (127%), while Emax values for U46619 were higher in tissues from patients without surgery for BPH (59%) compared to laser-enucleated tissues.ConclusionSymptom severity increases with α1-adrenergic, but not with non-adrenergic contractions in patients undergoing surgery for BPH. Endothelin-1-induced contractions are similar to noradrenaline-induced contractions. Conditions necessitating BPH surgery may not necessarily depend on α1-adrenergic tone, but may involve non-adrenergic contractions or factors beyond contraction.